Peranan Bank Wakaf Mikro dalam Pemberdayaan Usaha Kecil pada Lingkungan Pesantren - Muhammad Alan Nur; Rais Sani Muharrami; Mohamad Rahmawan Arifin (Journal of Finance and Islamic Banking, 2019)
The purpose of this study was to determine the effect of Micro Waqf Bank financing on the empowerment of micro-businesses in the al-Pansa boarding school environment. The study uses qualitative methods with a phenomenological approach. The population in this study are customers who are included in the first and second Halmi forces at the al-Pansa Micro Endowments Bank. In conducting data collection techniques used are observation, interviews, and triangulation. The data analysis uses the Miles and Huberman approach. The results showed that the financing and business assistance carried out by the Al-Pansa Micro Waqf Bank had an impact on an increase in the number of production members. This increase in production has led to an increase in business revenues and customer profits which has subsequently helped to improve the economic conditions of customers. Despite the increase, the increase has not increased significantly.